The Effect of Handover Training on Nurses' Communication Skills at Pembinaan Kesejahteraan Umat Muhammadiyah Surakarta - Fivin Titik Ningrum; Supratman Supratman; Faizah Betty Rahayuningsih (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2024)
Patient admissions help nurses identify service areas to improve patient safety Patient admissions help nurses identify service areas to improve patient safety. Effective communication between nurses and patients is very important in providing quality services. Inaccurate information can have a serious impact on patients, incidents are caused by poor communication, less than optimal communication. The aim of this research was to determine the effect of consideration training on nurses' communication skills in the inpatient room at the Surakarta Muhammadiyah Ummah Welfare Development Hospital. This research uses a preexperimental research method with one group pretest-posttest. The research sample was nurses who worked in inpatient rooms. Sampling was taken through purposive sampling, with the inclusion criteria of nurses with 1 year of work experience. The instruments used were a consideration and acceptance questionnaire adopted from Payne as well as a consideration and acceptance implementation checklist quoted from Parke & Mishkin. Data analysis used the Paired Sample-T test with a significance level of 5%, CI-95% confidence interval. The analysis results indicate that there is no significant difference in communication skills before and after the training (p=0.083). Handover training activities have no effect on nurses' communication skills, and they do not significantly improve the quality of nurses' communication abilities in the inpatient ward. Several things that can be recommended include a commitment to carry out considerations in the form of policies, direction and evaluation of the implementation of considerations, for the sake of continuity of nursing care which has an impact on increasing nurses' communication skills in implementing patient safety as well as adding samples to ensure sample representation in further research and optimize patient admission training by providing strict sanctions for nurses who do not carry out patient admission proceduresKeywords: Communication, Handover, Nursing, Skills, Training